EFFECT OF EXIT CONDITIONS ON SATURATION FLOW AT AN INTERSECTION APPROACH - Wibowo, 1Basuki
The control of traffic at highly saturated intersections in urban street networks has disclosed some unexpected difficculties. Among these has been a lack of success in coordinating traffic signals where the road links between signalized intersections contained long queues of stopped vehicles. The present research has definitively shown that saturation flow across a stopline is greatly affected by the presence of a downstream queue. Quantitative relationships were formulated from field experiments which led to defining the numerical function of saturation flow, and of the crossing time, for vehicles to enter and cross three study intersections in Indonesia. An ancillary problem encountered during the research was the need to express the traffic value of a motorcycle in terms of passenger car units for inclusion in the determination of saturation flows. This was accomplished by the use of a little-known method developed at the British Road Research Laboratory in 1964. Scraggs method derives from a theoretical consideration of headways of different types of vehicles travelling across a stopline in different sequences. Through testing of a stipulated necessary and sufficient condition, it was found that the method could be applied to the mixed vehicle flows observed at the Bandung research site. The result was determination of the passenger car unit value of motorcycles to be in range 0.60 to 0.64, depending upon the traffic lane used at a multi lane approach. The appropriate values were employed to determine the saturation flow of vehicles across the stopline. Direct observation of field data by video-tape recording, and subsequent analysis in the laboratory, enabled large amounts of data to be collected and evaluated to reach the trends and conclusions which are shown both graphically and in mathematical formulation. The present research showed the very critical conditions for exiting from a signal-controlled intersection when the exit provides little or no space for additional vehicles in a standing queue downstream. The research confirmed trends found by others for Thailand and the United States. Corollary to the main thrust of the research, speed/ density and speed/flow relations were found by transforming the equations of unoccupied space available from crossing time to speed and saturation flow at the study intersections. The effect of unoccupied space available downstream was shown by identifying each plotted point on the speed/density and speed/flow graphs with the additional parameter.